2015
DOI: 10.1002/14651858.cd010868.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for dissociated vertical deviation

Abstract: Background The term “strabismus” describes misalignment of the eyes. One or both eyes may deviate inward, outward, upward, or downward. Dissociated vertical deviation (DVD) is a well-recognized type of upward drifting of one or both eyes, which can occur in children or adults. DVD often develops in the context of infantile- or childhood-onset horizontal strabismus, either esotropia (inward-turning) or exotropia (outward-turning). For some individuals, DVD remains controlled and can only be detected during clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
(95 reference statements)
0
25
0
Order By: Relevance
“…Different treatment methods such as superior rectus recession (SRR), chemodenervation, anterior transposition of the inferior oblique muscle, resection of the inferior rectus muscle and their combined surgeries are recommended in the surgical treatment of the DVD. 4,16 Akar et al compared the surgical results and possible complications of three surgical techniques namely SRR, posterior fixation suture surgery with the anterior transposition surgery and the anterior transposition surgery in DVD. 17 In this study, 22 (69%) out of 32 eyes who underwent SRR surgery were considered successful (<5 prism diopter), while residual DVD was observed in other patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different treatment methods such as superior rectus recession (SRR), chemodenervation, anterior transposition of the inferior oblique muscle, resection of the inferior rectus muscle and their combined surgeries are recommended in the surgical treatment of the DVD. 4,16 Akar et al compared the surgical results and possible complications of three surgical techniques namely SRR, posterior fixation suture surgery with the anterior transposition surgery and the anterior transposition surgery in DVD. 17 In this study, 22 (69%) out of 32 eyes who underwent SRR surgery were considered successful (<5 prism diopter), while residual DVD was observed in other patients.…”
Section: Discussionmentioning
confidence: 99%
“…The approach in vertical strabismus is commonly case-bycase. [3][4][5][6] Our aim was to analyze our cases with vertical deviations and compare our outcomes among vertical strabismus cases with various etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…It was an abnormal vertical movement of eye ball, contradictory with the role of nerve domination [1]. When DVD coexisted with inferior oblique over-action (IOOA), inferior oblique anterior transposition (IOAT) was recommended [2][3][4][5][6][7]. It was an ideal method to reduce the strength of inferior oblique and restrict floating phenomenon of DVD synchronously.…”
Section: Introductionmentioning
confidence: 99%
“…It was considered to be an ideal method to reduce the strength of the inferior oblique muscle and simultaneously restrict the floating phenomenon of DVD. Most clinicians suggested that binocular DVD should be treated with binocular surgery, especially for symmetric DVD [3,5,7]. However, treatment decisions are more complex in asymmetric DVD, in which bilateral asymmetric [8,9,10] or unilateral [4] surgery may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…DVD is usually bilaterally. Asymmetric DVD is probably associated with unequal IOOA or superior rectus overaction[7]. The management of DVD is challenging for strabismus surgeons.…”
mentioning
confidence: 99%